Assessment of The Bethesda System for Reporting Thyroid Cytopathology: Surgical and Long-Term Clinical Follow-up of 2, 893 Thyroid Fine-Needle Aspirations. Issue 4 (15th July 2019) - Sauter, Jennifer L; Lehrke, Heidi; Zhang, Xiaotun; Al Badri, Osamah T; Rodriguez-Gutierrez, Rene; Delivanis, Danae A; Singh Ospina, Naykky; Donegan, Diane; Hamidi, Oksana; Iñiguez-Ariza, Nicole; Sharma, Anu; Kittah, Nana Esi N; et al.
Abstract: Objectives: Long-term follow-up is important for determining performance characteristics of thyroid fine-needle aspiration (FNA). Methods: Histologic or 3 or more years of clinical follow-up was used to calculate performance characteristics of thyroid FNA before and after implementation of The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC). The impact of noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) classification was also investigated. Results: Follow-up was obtained for 1, 277/1, 134 and 1, 616/1, 393 aspirates/patients (median clinical follow-up, 9.9 and 4.4 years, pre- and post-TBSRTC, respectively). Nondiagnostic, suspicious for follicular neoplasm, and suspicious for malignancy (SFM) diagnoses decreased and benign diagnoses increased post-TBSRTC, while atypical rate remained less than 1%. Negative predictive value for benign nodules and positive predictive value (PPV) for SFM increased significantly. Eleven nodules were reclassified as NIFTP, slightly decreasing PPV/risk of malignancy (ROM). Conclusions: Appropriate ROM for thyroid FNA can be achieved through application of TBSRTC terminology with minimal use of atypical category.